Monitoring Soil Water Content and Measurement Depth of Cosmic-Ray Neutron Sensing in the Tibetan Plateau - Wang, Xin; Liu, Rong; Köhli, Markus; Marach, J.; Wang, Zuoliang (Journal of hydrometeorology, 2025)
This work aims at evaluating the potential application of two cosmic-ray neutron sensing (CRNS) soil water content (SWC) retrieval methods and discusses the effective measurement depth of CRNS retrieval and vertical weights of different layers in a semihumid alpine meadow on the Tibetan Plateau. In this study, the widely used N0 method and the latest published method derived from physical principles named the universal transport solution (UTS) were used for SWC estimation during the whole nonfrozen season on the Tibetan Plateau. The N0 and UTS methods successfully retrieved the SWC on the Tibetan Plateau, and their variations were generally consistent. The effective measurement depths calculated by the N0 and UTS methods showed similar fluctuation patterns, ranging from 9.7 to 14.5 cm and 17.8 to 20 cm, with mean values of 12.0 and 19.2 cm, respectively. This work verified that the weighting methods of the N0 and UTS models provided credible performance for the effective measurement depths. The N0 method provided measurement depths more close to the surface, and the UTS method yielded slightly deeper averages. The UTS equation had a more sensitive response to periods of low precipitation. Including detailed Ultra Rapid Neutron-Only Simulation (URANOS) Monte Carlo simulations of the full time series, we find specifically an excellent agreement in the summer period. Our analysis suggests that CRNS is a promising innovation for SWC measurement and can be extended in its application at hectometer scales to monitor SWC in the Tibetan meadow ecosystem. Significance Statement The purpose of this study is to better understand if cosmic-ray neutron sensing (CRNS) has the potential to sense soil water content (SWC) for the Tibetan meadow ecosystem with harsh climate conditions. Techniques for measuring SWC have evolved over many decades, from point-scale measurements of a few meters to satellite-based remote sensing methods of several kilometers, each with advantages and disadvantages. This is important because CRNS has emerged to fill the scale gap between point measurements and microwave remote sensing methods. The results are helpful in assessing the applicability of CRNS in alpine meadow ecosystems on the Tibetan Plateau.